Strengthening Adaptive Capacity of Extensive Livestock Systems for Food and Nutrition Security and Low-emissions Development in Eastern and Southern Africa: Training Report on Food and Nutrition Security - Munjoma-Muchinguri, P.; Makonnen, Brook T. (International Livestock Research Institute, 2024)
This report details a virtual Training on Food and Nutrition Security held on 9 May 2024 on the Zoom platform. The training was part of the fulfillment of the objectives for the ACIAR (Australian Centre for International Agricultural Research) Extensive Livestock Systems project in Eastern and Southern Africa (ESA). A total of 17 participants representing Ethiopia, Kenya and Zimbabwe attended the three-hour session from 9.00 am to 12.00 noon. The participants were mainly from academic backgrounds engaged in the study as supervisors or students.